Klotho protein in men with type 2 diabetes mellitus blood and its association with cardiometabolic risk factors - O. V. Timoshchenko; E. M. Stakhneva; Yu. I. Ragino; Yu. P. Nikitin (Сибирский научный медицинский журнал, 2021)
The aim of the study was to investigate Klotho protein levels in men with type 2 diabetes blood and its associations with several cardiometabolic risk factors. Material and methods. The study included 37 men with diabetes and 141 men without diabetes. Fasting blood samples were collected to measure Klotho protein levels and some biochemical parameters. Results and its discussion. The Klotho protein level in men with diabetes was significantly lower than in men without diabetes (374 [117; 500] and 515 [315; 1009] pg/dl, p<0.0001). Among the examined men with diabetes with a glomerular filtration rate of less than 60 ml/min/1.73 cm2, the concentration of Klotho protein was 4 times lower than in the comparison group (104 [93; 118] and 413 [147; 535] pg/dl, p = 0.014) In men with diabetes, the Klotho protein was inversely correlated with the ratio of waist to hip circumference (-0.329; p = 0.047). But with multivariate analysis, only a tendency towards a negative association of the Klotho protein with abdominal obesity was determined (-0.385, p = 0.078). Conclusion. The content of Klotho protein in men with diabetes is significantly lower, especially in middle-aged men and in those with a reduced glomerular filtration rate. In men with diabetes, the Klotho protein has a negative correlation with the presence of abdominal obesity. In a multivariate analysis among men with diabetes, the Klotho protein tends to be inversely associated with the presence of abdominal obesity.